Secular and liberal education in the nations building process, ideas and history in america. The colombian case, to the late nineteenth and early twentieth century. (2019)
This article discusses aspects in the fi eld ofeducation and university in North and Latin America in thecolonial years, and the late nineteen than early twentiethcentury, especially in countries like Argentina, Chile,Brazil and The Colombia’s Case, that requires specialconsideration based on the ideological, political andphilosophical assumptions underlying the offi cial educationin Colombia, and the secular and liberal responses to suchconsiderations on colonial, republican and constitutionalorders. It is concluded that in the formation of the Americanrepublics, there are similar phenomena in terms of war facts,declarations of independence, the formation of creole elitesto impose their liberal speeches in most of the time andeducation systems assuming that it will serve to establishindependent and prosperous republics.